Efektivitas Pembelajaran Tambahan Pagi untuk Meningkatkan Keterampilan Berbicara Bahasa Arab Bagi Santri Pondok Pesantren Al-Karamah Bima - Hamidatul Latifah; Mappasiara (Al Asma: Journal of Islamic Education, 2023)
This study aims to determine the effectiveness of additional morning lessons in improving Arabic speaking skills for students at the Al-Karamah Bima Islamic boarding school. This type of research is descriptive qualitative research. This research was conducted at the Al-Karamah Bima Islamic Boarding School. The subjects of this study were educators in the additional morning lessons and 19 (nineteen) students in grade 3 science. There are three data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Based on the results of observations and interviews, it can be concluded that 1) the implementation of additional morning learning is carried out after the morning prayer, by giving several mufradats of approximately three or five mufradat and additional morning learning is carried out every day so that students master Arabic. 2) the results of additional morning learning are an increase both in terms of grades and in terms of student understanding. 3) the effectiveness of additional morning learning in improving Arabic speaking skills for students is very effective and appropriate in achieving the goals to be achieved by Islamic boarding schools, it is proven that most of the students have experienced an increase from the results of observations, interviews, and the scores obtained.